Biological Flora of the British Isles: Epipactis palustris. (29th July 2014) - Jacquemyn, Hans; Brys, Rein; Hutchings, Michael J.
Summary This account presents information on all aspects of the biology of Epipactis palustris (L.) Crantz that are relevant to understanding its ecological characteristics and behaviour. The main topics are presented within the framework of the Biological Flora of the British Isles: distribution, habitat, communities, responses to biotic factors, responses to environment, structure and physiology, phenology, floral and seed characteristics, herbivores and disease, history, and conservation. Epipactis palustris is native to Britain, being widely distributed throughout England and Wales, but is less common in the north. Although absent from most of Scotland, it occurs as far north as Perthshire. It is widely distributed in Ireland. The species extends throughout most of Europe, occurring as far east as Mongolia and the north of Turkey, but it is absent from the southern Mediterranean region. Epipactis palustris grows mainly in full sunlight, rarely under shade, and on calcareous, but nutrient‐poor, moist to wet substrates. It favours flushed or seasonally inundated areas in which the intensity of competition from other vegetation is low. It is most commonly found in wet dune slacks, calcareous fens and on peat, but it also occurs on sandy substrates overlying heavy clay or loamy soils. Occasionally, it can also be found near the top of slopes in chalk downland. Epipactis palustris multiplies both by vegetative propagation and sexual reproduction. Vegetative propagation involves the production of regularly branched rhizomes. It flowers in Britain from the end of June until the beginning of September. The flowers produce nectar, which is often colonized by bacteria and to a lesser extent by yeasts. The species is pollinated by a wide range of insects, including honeybees, flies, wasps, beetles, bumblebees and ants, but is also capable of limited spontaneous autogamy. The most efficient pollinators are small bees and solitary wasps. Fruit production is generally high (>80% of the flowers produce capsules). Epipactis palustris is vulnerable to changes in soil water level and to substrate nutrient enrichment. It has suffered a strong decline in its distribution range in Britain, with most losses of local populations occurring before 1930. Habitat destruction and drainage of marshes and fens appear to be the most common causes for the decline of the species. Restoration of old wet dune slacks by topsoil removal and addition of hay from neighbouring vegetation has been successful in encouraging colonization and establishment of populations of the species within a few years. Cessation of draining of mires may also promote the long‐term survival of populations of the species.